The Molecular Pathogenesis of Sarcopenia/Frailty in Cirrhosis - Jiao, Huanli; Wang, Han; Li, Jia; Yang, Ziyi; Sun, Chao (Seminars in Liver Disease, 2025)
Cirrhosis is an important cause of morbidity and death in patients with chronic liver disease. It can be divided into compensatory and decompensated stages. During the decompensation period, complications such as esophageal and gastric varices hemorrhage, hepatic encephalopathy, infection, and hepatorenal syndrome are often incurred, which has a high mortality rate and leverages huge economic burden on society, healthcare resources, and individuals. Sarcopenia and frailty are common in patients with cirrhosis. The pathogenesis of sarcopenia and frailty in the context of cirrhosis is complicated and multifactorial, including overwhelming systemic inflammation, imbalance of muscle protein metabolism, malnutrition, endocrine and metabolic dysfunctions, intestinal microecological disorders, lack of physical exercise, and other aspects. Notably, accumulating evidence implicates that many patients experience sarcopenia/frailty even before the onset of liver cirrhosis. In this regard, the magnitude of liver fibrosis is closely linked to the progression of sarcopenia with reciprocal impact. In conclusion, this review article will shed light on the pathogenesis of cirrhosis complicated with sarcopenia/frailty, aimed at facilitating early diagnosis and effective management.
Keywords: cirrhosis; sarcopenia; frailty; pathogenesis; molecular mechanism